IMPROVED METHOD OF LASER CORRECTION OF ATROPHIC SCARS - Рузін, Г.П. (World of Medicine and Biology, 2016)
During the study following parameters were taken into account: the depth of the scar, the scar area, consistency, color, condition of the scar microcirculation. Due to the use of laser in bench regeneration Q - SW pulse duration of 1.2 ns is obliteration of the vessel in the bottom of the hem with no impact on its upper layers and the surrounding tissue. Thus, the use of advanced laser correction method (a one-time procedure of laser exposure) provides a stable clinical outcome, the reducing of the depth of the scar (an average of 2 mm), softening texture and turning color to normal (common to surrounding skin). Due to the short term of the laser impact (1 - 2 ns), thanks to technology Q – C, method is painless and safe, and does not affect the surrounding tissue.